A multi-pollutant assessment of preconception persistent endocrine disrupting chemicals and incident pregnancy loss - Melissa M. Smarr; Sedigheh Mirzaei Salehabadi; Dana Boyd Barr; Germaine M. Buck Louis; Rajeshwari Sundaram (Environment International, 2021)
Background: A few endocrine disrupting chemicals (EDCs) have been associated with pregnancy loss often as reported by women, though there has been no study of EDC mixtures and pregnancy loss in keeping with the nature of human exposure. Objectives: To investigate preconception exposure to a mixture of EDCs to identify important drivers and inform multi-pollutant models of EDCs in relation to incident human gonadrophin chorionic (hCG) pregnancy loss. Methods: A cohort of 501 couples were recruited from the general population and prospectively followed until a hCG-confirmed pregnancy or 12 months of trying to become pregnant. Pregnant (n = 344; 69%) women were followed daily through seven weeks post-conception then monthly until delivery. Loss was defined as conversion to negative pregnancy test or a clinical diagnosis. Preconception exposure assessment of EDCs included sixty-three serum chemicals and three blood metals. EDCs were measured using isotope dilution gas chromatography-high resolution mass spectrometry or high-performance liquid chromatography-tandem mass spectrometry, and inductively coupled plasma-mass spectrometry, respectively. Using elastic net variable selection to identify important factors from the exposure mixture, EDC levels and covariates were then included in Cox proportional hazard models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) of time-to-pregnancy loss in multi-pollutant models. Results: Incidence of hCG pregnancy loss was 28%. Nine EDCs of the sixty-six chemical mixture were associated with pregnancy loss; HRs were elevated for polychlorinated biphenyl 194, 2-(N-methyl-perfluorooctane sulfonamido) acetate, polybrominated diphenyl ether 28, and cadmium, even in sensitivity models adjusting for male partners’ EDC concentrations. In final multivariable multi-pollutant Cox proportional hazard models, female partners’polybrominated diphenyl ether 28 (aHR = 1.16, 95% CI: 1.02, 1.31) and cadmium (aHR = 1.23, 95% CI: 1.07, 1.40) remained associated with hCG pregnancy loss. Female partners’ preconception serum polychlorinated biphenyl 194 and 2-(N-methyl-perfluorooctane sulfonamido) acetate concentrations were consistently inversely associated with loss [(aHR = 0.72, 95% CI: 0.56, 0.92) and (aHR = 0.79, 95% CI: 0.65, 0.95), respectively]. Conclusion: Assessing exposure to a mixture of 66 persistent EDCs, females’ preconception concentrations of polybrominated diphenyl ether 28 and cadmium were positively associated with incident hCG pregnancy loss in a cohort of couples from the general population trying for pregnancy.